Ultrasonographic Estimation of Thyroid Gland Volume Among Bangladeshi Population (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Ultrasonography is the most commonly usedmethod to determine thyroid gland volume because of its superficial anatomical placement. Aim of this study was to evaluate the volume of normal thyroid gland and its correlation with Body Mass Index (BMI) among Bangladeshi population from Chattogram district.  Materials and methods: This cross-sectional study was carried out in the Department of Anatomy, Chittagong Medical College, from July 2022 to June 2023 among 200 (100 male, 100 female) Bangladeshi population of Chattogram district. Expert sonologists performed thyroid ultrasound and calculated thyroid gland volume of each lobe. The statistical analysis was done using SPSS version 26 and p-value was considered significant if it was 0.05). Spearman’s correlation test revealed that total thyroid gland volume was negatively correlated with BMI (p=0.440).Conclusion: Result of the present study provides some baseline data about normal thyroid gland volume of Bangladeshi population of Chattogram district which will help to establish the reference valuesfor the physicians and surgeons to deal with various thyroid pathologies.JCMCTA 2024 ; 35 (2) : 112-116